The future of integrative health and medicine in Saudi Arabia - Mohamed K.M. Khalil; Sulaiman Al-Eidi; Meshary Al-Qaed; Saud AlSanad (Integrative Medicine Research)
Saudi Arabia is witnessing a healthcare transformation to face the challenges of the increased burden of noncommunicable diseases and to maintain the quality of healthcare services. However, in Saudi Arabia, where low back and neck pain, depressive disorders, migraine, diabetes, and anxiety disorders cause the most disability, a broader way of integrative health approach is needed to foster healthy lives and promote well-being for all ages. In the presence of the advanced modern medicine healthcare system in Saudi Arabia, the traditional medicine healing system is being used by a substantial proportion of Saudis but like a shadow healthcare system. This phenomenon of using two healthcare systems reflects a need for an integrative healthcare system. Integrative medicine or approach is about bringing traditional, complementary, and modern medicine in a harmonized system of healthcare which can give a high return and save cost. The rationale behind integrative medicine is to include the best practices of both conventional and complementary therapy, uniting these practices into an integrative approach. Pain management, care of cancer patients, and behavior change are among the leading areas of integration models that should be included in healthcare transformation in Saudi Arabia. Investment in behavior change and well-being outside the boundaries of the healthcare system in the Saudi 2030 vision will have more impact on health and wellness of the Saudi citizen in the face of the epidemics of the lifestyle diseases. Models of integrative medicine during the healthcare transformation can be developed, evaluated, and replicated. Keywords: Cupping, Integrative medicine, Saudi Arabia, Healthcare transformation